The philosophy of logical practice. (3rd April 2022) - Martin, Ben
Abstract : While we now have an increasingly detailed understanding of the varied goals and methods that constitute the sciences and mathematics, our understanding of logic as a research area lags behind. A significant reason for this deficiency is that, unlike in the philosophies of science and mathematics, philosophers of logic have yet to embrace a practice‐based approach to their field, re‐orientating their attention towards logic as it is actually practised by logicians. This paper makes the case for a new area of research, the philosophy of logical practice, to sit alongside traditional philosophy of logic and systematically investigate logic's aims and methodologies using the practice‐based approach.